2020
DOI: 10.1186/s13071-020-04118-x
|View full text |Cite
|
Sign up to set email alerts
|

Predominant risk factors for tick-borne co-infections in hunting dogs from the USA

Abstract: Background Both incidence and geographical range of tick-borne disease has increased across the USA. Similar to people, dogs are hosts for Anaplasma spp., Babesia spp., Ehrlichia spp. and Borrelia burgdorferi. Dogs also share our homes and beds, making them both a sentinel for the ticks in our backyards but also increasing our exposure to ticks. Measures to better track, prevent, and/or treat tick-borne diseases in companion animals can lead to better control and prevention of human tick-borne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…burgdorferi prevalence was highest in the Northeast, as expected from prior nationwide study (Bowman et al 2009, Mahachi et al 2020, and owing in large part to vector species distributions. For Anaplasma spp., we found the highest prevalence in the Northeast ( p = 0.041) similar to findings in hunting dogs (Mahachi et al 2020). We found that the highest seroprevalence for antibodies to T. cruzi was in the southeastern United States, where there is a robust enzootic transmission cycle Montgomery 2009, Bern et al 2011), and the detected exposures in dogs outside this range likely occurred predeployment while training in the south (Meyers et al 2020b).…”
Section: Possupporting
confidence: 65%
See 3 more Smart Citations
“…burgdorferi prevalence was highest in the Northeast, as expected from prior nationwide study (Bowman et al 2009, Mahachi et al 2020, and owing in large part to vector species distributions. For Anaplasma spp., we found the highest prevalence in the Northeast ( p = 0.041) similar to findings in hunting dogs (Mahachi et al 2020). We found that the highest seroprevalence for antibodies to T. cruzi was in the southeastern United States, where there is a robust enzootic transmission cycle Montgomery 2009, Bern et al 2011), and the detected exposures in dogs outside this range likely occurred predeployment while training in the south (Meyers et al 2020b).…”
Section: Possupporting
confidence: 65%
“…B. burgdorferi prevalence was highest in the Northeast, as expected from prior nationwide study (Bowman et al 2009, Mahachi et al 2020, and owing in large part to vector species distributions. For Anaplasma spp., we found the highest prevalence in the Northeast ( p = 0.041) similar to findings in hunting dogs (Mahachi et al 2020).…”
Section: Possupporting
confidence: 64%
See 2 more Smart Citations
“…The prevalence rate was higher in the Northeastern U.S. (12.1%), where L. infantum is also enzootic among dogs [ 142 ]. Although the U.S., particularly the Eastern U.S., has relatively high seropositivity for canine borreliosis [ 143 ], there is currently limited published data on co-infection with CanL. In Europe, canine Borrelia spp.…”
Section: Bacterial Co-infectionsmentioning
confidence: 99%